FACTORS AFFECTING THE AGE OF MENOPAUSE IN PADANG CITY IN 2023 - Rizky Rivonda Bennovry; Syahredi SA; Bobby Indra Utama (Andalas Obstetrics And Gynecology Journal, 2024)
AbstractMenopause is characterized by a consecutive period of amenorrhea lasting 12 months without anyunderlying causes or surgical interventions. The age at which menopause occurs can be influenced byvarious factors, including menarche, number of childbirths, body mass index, and the utilization ofhormonal contraceptives. This study aims to determine the factors that influence the incidence ofmenopause in Padang. This study is an analytical research with a cross-sectional study design. Theresearch was conducted in the working areas of all primary public health centers in Padang fromJanuari 2023 to September 2023. The sample consisted of middle-aged women who visited theworking areas of all primary public health centers during the study period. This study is using aquestionnaire as the research instrument and employing the simple random sampling technique toobtain a sample size of 124 participants. The data analysis was conducted using the Chi- Square test,and utilize the statistical software SPSS. A significant relationship between variables was defined if thep-value < 0.05. The results of this study revealed that the majority of respondents experienced earlymenarche (36.3%), had multiparous pregnancies (33.9%), had underweight body mass index (33.1%),used hormonal contraceptives (52.4%), and experienced late menopause (40.3%). The analysisshowed a significant relationship (p<0.05) between the age of menarche (p=0.036) and parity(p=0.002) with the occurrence of menopause. However, there was no significant relationship (p>0.05)between body mass index (p=0.141) and history of contraceptive use (p=0.069) with the occurrenceof menopause. This study found a significant relationship between the age of menarche and paritywith the occurrence of menopause, while there was no significant relationship between body massindex and history of contraceptive use with the occurrence of menopause among middle-aged womenvisiting the primary public health center areas in Padang.